El camino de verdad, justicia y reparación de las familias víctimas de las masacres carcelarias en Ecuador (Tema Central) - Bastias Robayo, Fernando (2024)
Ecuador is experiencing the direct outcomes of the prison crisis, with over 600 incarcerated individuals murdered due to the actions and omissions of the State and its public institutions. These events not only create a context of human rights violations for those in prison but also for their families. This article presents the families of incarcerated individuals as direct victims of the prison crisis and as a group of human rights defenders seeking, through love, resilience, and hope; offer peace, justice, and reparation to all victims of violence in Ecuador.